2020
DOI: 10.1093/jtm/taaa192
|View full text |Cite
|
Sign up to set email alerts
|

Social consequences of mass quarantine during epidemics: a systematic review with implications for the COVID-19 response

Abstract: Four billion people worldwide have experienced COVID-19 confinement. Such unprecedented extent of mobility restriction to curb the COVID-19 pandemic may have profound impacts on how individuals live, travel, and retain well-being. This systematic review aims to identify: 1) the social consequences of mass quarantine—community-wide movement restrictions—during previous and current infectious disease outbreaks, and 2) recommended strategies to mitigate the negative social implications of COVID-19 lockdowns. Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
166
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(183 citation statements)
references
References 74 publications
(256 reference statements)
3
166
0
14
Order By: Relevance
“…Although studies have shown these mitigation strategies to be effective, careful consideration also need to be given to the social, political and economic impacts for those living in vulnerable conditions. Isolation and lockdowns can have negative social consequences such as impacts on mental health, education, food security and access to health care especially for those living in socially and economically vulnerable conditions [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have shown these mitigation strategies to be effective, careful consideration also need to be given to the social, political and economic impacts for those living in vulnerable conditions. Isolation and lockdowns can have negative social consequences such as impacts on mental health, education, food security and access to health care especially for those living in socially and economically vulnerable conditions [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most governments have responded with public health measures such as isolation, contact tracing, quarantining of contacts, community quarantine including social distancing 57 and varying degrees of lockdowns. 58 The responses have caused global social and economic disruption, 59 economic losses, downturn of the tourism industry and a global recession. Many educational institutions have been partially or fully closed.…”
Section: Public Health Emergency Of International Concern (Pheic)mentioning
confidence: 99%
“…Wide-ranged population-based interventions, which indiscriminately prevent transmission at the pre-symptomatic and symptomatic phase ( Fig. 1 ), might have greater effects but also cause significant societal and economic impacts [ 30 ]. Therefore, Taiwan’s blended approach aims to make the targeted case-based interventions more extended to cover pre-symptomatic/asymptomatic patients, and make the extended population-based approach more targeted to preserve public health and healthcare capacities ( Fig.…”
Section: Pre-symptomatic/asymptomatic Transmission and Its Implicatiomentioning
confidence: 99%